La nouvelle interlope 1. - Bertoin, Arielle; Bouchain, Patrick; Boussiron, Xavier; Coste, Michel; Delay, Alexandre; Giquel, Pierre; Guezenger, Claire; Moriceau, Laurent; Parè, Jean-Christophe; Petiteau, Jean-Yves; Raynaud, Patrick; Restany, Pierre (Nantes : ERBAN - Ecole Régionale des Beaux-Arts de Nantes, 1998)
Moriceau, Laurent ; Hyber, Fabrice ; Eric, Made in ; ArnaudLabelle-Rojoux ; Savatier, Pierre ; Mogarra, Joachim ; Ellena, Veronique ; Magasin, Grand ; Sorin, Pierrick ; Orlan ; Delay, Alexandra ; Robbe, Hervé ; Parè, Jean-Christophe ; Brumachon, Claude ; Lamarche, Benjamin ; Lizèrie, Jacques ; Manga, Gérard ; Schaerf, Eran ; Mosler, Mariella ; Ming, Yan Pei ; Leclercq, Aurélia ; Blin, Isabella ; Lacaton, Anne ; Vassal, Jean-Philippe ; Oxymore ; Fillion, Odile ; Soler, Francis ; 10, Blockhaus DY ; Forestier, Frédéric ; Séchas, Alain ; Coignet, Jean-Gabriel ; Mach, David ; Bouchain, Patrick ; 1998, Post-Diplôme ; Restany, Pierre ; Kuizine, La ; Tanguy, Cédric ; Hains, Raymond ; Petiteau, Jean-Yves ; Bertoin, Arielle ; Coste, Michel ; Giquel, Pierre ; Boussiron, Xavier ; Guezengar, Claire
La nouvelle interlope 1998, Ecole Régionale des Beaux-Arts de Nantes, 1998
Frans
boek